Preparation and characterization of polyimide membrane impregnated with silver nanoparticles for gas separation - Lim, Boon Hao (2016)
P84 polyimide is one of the preferred materials to form membrane due to its high selectivity and excellent anti-plasticization properties against carbon dioxide. Silver nanoparticle has been gaining popularity due to its antimicrobial ability. Hence, this study investigated the effects of silver nanoparticle on the performance of P84 polyimide membrane.